Persepsi Bauran Pemasaran terhadap Kepuasan Konsumen dan Hubungannya dengan Minat Berkunjung Ulang pada Mangsi Coffee - NI WAYAN VIVI OVITA; I G A OKA SURYAWARDANI; I DEWA GEDE AGUNG (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Perception of Marketing Mix on Consumer Satisfaction and The Relations withIntention to Revisit in Mangsi CoffeeMangsi Coffee is one coffee shop in Denpasar area, as one of the tourism facilities inBali. Rapid market competition resulted in Mangsi needing to pay attention to customersatisfaction. Consumer satisfaction is measured through consumer perceptions byassessing the marketing strategies that have been applied. The purpose of this study is toidentify indicators forming marketing mix variables that affect customer satisfaction andits relationship with intention to revisit in Mangsi Coffee. This research was conductedat Mangsi Coffee Sanur and Merdeka with 100 respondents. The analysis used isStructural Equation Model (SEM). The results showed that the product variable wasformed by 5 brand indicators, taste, presentation, aroma, and product variation. Pricevariables are formed by 3 indicators, namely affordability, price suitability, and pricecompetitiveness. Promotion variables are formed by 4 indicators of service, media,quality, and quantity of promotion. Place variables are formed by 4 indicators ofcomfort, decoration, cleanliness and service. The results of the direct influence ofexogenous variables on endogenous variables with a significant level is 5% (0.05)indicate that all direct relationships have a significant and positive effect. The influenceof the most significant marketing mix variables on customer satisfaction is thepromotion variable is 21.7% (0.217) with p-Value is 0.065. The effect of variablecustomer satisfaction on intention to revisit is 77.3% (0.773) with a p-Value is 0.000.The results showed that consumer satisfaction at Mangsi Coffee was good but anevaluation of marketing strategy was needed if a marketing strategy was changed.